Edukacyjne cechy gamingu - Kowalczuk, Karol (Homo Ludens, 2020)
The modern development of the gaming space is often seen through the prism of the attractiveness and success. Thanks to their features, computer games are not only the foundation of the modern world of entertainment, but also become a significant area in many spaces of social life – also in education. For a long time they have been perceived as notdidactic and not-educational, but currently they constitute an attractive educational strategy from the point of view of young students. The use of elements of computer games in education is becoming more common and more and more extensive. The main role in this process is played by the need to adapt the teaching message to the modern digital student, the polisensoricity and dynamics of the gaming world is a determinant of attractiveness for them. On the other hand, the contemporary school is faced with the need to update the content presented by it for the “digital natives”. Computer games fit into solving many teaching problems thanks to their features and the undoubted educational potential which only needs to be noticed.